MENINGKATKAN KETERAMPILAN SISWA MENULIS TEKS REPORT DENGAN PEMBELAJARAN MIND MAPPING BERBASIS MULTIMEDIA - Dedi Hendrianto, Santi Hendrayani (Journal Of Language Education and Development (JLed), 2019)
The article provides information about the implementation multimedia-based on Mind Mapping learning models among students IX students of SMP N 19 Batanghari and the improvement of their writing skill on report text through the use of this model. This research is a classroom action research which conducted in two cycles. The subject of this research is class IX students of SMP N 26 Batanghari with 33 students as participant . The object of the research is the improvement of writing skill in report text by using multimedia-based Mind Mapping. The data taken from observation, video recording and tests were analyzed by using qualitative and quantitative descriptive analysis. The results of the study show that there is an improvement of students' writing skill and learning outcomes through the multimedia-based Mind Mapping learning model. It can be seen from 2 cycles that are carried out. In the pre-cycle student success rate of 53, 60 with a low category, the first cycle of student success rates reached an average of 62.22 with a low category, in the second cycle the average student success increased significantly to 75.00.